2016
DOI: 10.1209/0295-5075/114/47011
|View full text |Cite
|
Sign up to set email alerts
|

Structure and dielectric dispersion in cubic-like 0.5K 0.5 Na 0.5 NbO 3 -0.5Na 1/2 Bi 1/2 TiO 3 ceramic

Abstract: The nature of the cubic-like state in the lead-free piezoelectric ceramics 0.5K0.5Na0.5NbO3-0.5Na0.5Bi0.5TiO3 (KNN-50BNT) has been examined in detail by synchrotron x-ray diffraction (SD), selected area electron diffraction (SAED), neutron diffraction (ND), and temperature dependent dielectric characterization. The SD pattern of KNN-50BNT presents a pure perovskite structure with pseudocubic symmetry. However, superlattice reflections were observed by SAED and completely indexed by tetragonal symmetry with P4b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The variation in the tetragonality c / a will be closely related to the variation in ferroelectric properties and Curie temperatures . Similar cases could be found in Bi(Ni 2/3 Ta 1/3 )O 3 ‐PbTiO 3 systems …”
Section: Resultssupporting
confidence: 64%
“…The variation in the tetragonality c / a will be closely related to the variation in ferroelectric properties and Curie temperatures . Similar cases could be found in Bi(Ni 2/3 Ta 1/3 )O 3 ‐PbTiO 3 systems …”
Section: Resultssupporting
confidence: 64%
“…In order to extend materials' applicability to modern electronics, the information on local structure and physical properties is of great interest for fundamental studies . It is reported that a re‐entrant relaxor behavior is presented in BaTiO 3 –BiScO 3 , BaTiO 3 –Bi(Zn 2/3 Nb 1/3 )O 3 , and (K 0.5 Na 0.5 )NbO 3 –(Na 1/2 Bi 1/2 )TiO 3 . Meanwhile, the similar behaviors have been reported in Pb/Bi–based perovskites, such as (Ba 0.925 Bi 0.05 )(Ti 1‐ x /100 Sn x /100 )O 3 and Pb 0.76 Ca 0.24 TiO 3.…”
Section: Introductionmentioning
confidence: 73%
“…Due to the size and polarization of polar clusters decrease with increasing temperature, a frequency dispersion of dielectric permittivity is presented. In addition, the lattices outside the polar clusters constrain the mobility and temperature response of the clusters …”
Section: Introductionmentioning
confidence: 99%
“…[39] The long relaxation time and the small change in them (10 -5~1 0 -2 s) in the studied temperature range suggest: (i) a mixture of the time response of the R3c and P4bm polarization mechanisms (ii) minor changes in the size of the PNRs [40] and (iii) large size of the PNRs. Our previous work [40][41][42] reported that a coexistence of R3c and P4bm phase was evident in BNT-KNN ternary systems. Both R3c and P4bm phases are present on a nanoscale level and show a high thermal stability.…”
Section: Results and Discussion-mentioning
confidence: 99%